Strategies to Strengthen the Affective Domain in Learning Pancasila and Citizenship Education for Class XII Students of MAN 4 Pandeglang - Uus Fujiana; Damanhuri Damanhuri; Wika Hardika Legiani (Institut Pendidikan Indonesia, 2022)
This study aims to determine the strategies to strengthen the affective domain in Civics learning in class XII students and to determine the inhibiting and supporting factors in implementing the affective domain strengthening strategy in Civics learning in class XII students at MAN 4 Pandeglang. This research uses a type of qualitative approach with descriptive methods. The results found were that the strategy of strengthening the affective domain of students used learning models and methods aimed at improving the affective domain of students for the better, such as the habituation model in the form of assignment methods and monitoring good attitudes and behavior of students, exemplary models in the form of method of displaying good attitude and behavior. The strategy to strengthen the affective domain can run well and students can follow and be able to achieve the goals of strengthening the affective domain. Then the way to overcome the obstacles experienced in implementing the strategy to strengthen the affective domain in Civics learning is to use a personal approach to students, especially students whose affective domain or attitude is lacking and also students who experience difficulties in learning.